A children's space? Participation in multi‐agency early intervention. Issue 4 (9th March 2017) - Lucas, Steven
Abstract: The common assessment framework provides a model of early intervention, which is familiar in local authorities throughout England, and asserts a participatory framework of child and family engagement. This article draws on data from a research project undertaken in 1 local authority in the Midlands of England, to explore the experiences of children, young people, and their families, who were engaged in the process of multi‐agency early intervention. The article considers the young people's involvement, including their accounts of attending common assessment framework meetings, and their engagement by practitioners. The research found that young people's participation was limited. The findings suggest that this is, in part, a response to disciplinary discourses around schooling and attendance. In addition, the narratives of parents and young people showed that under‐resourcing of work with young people meant that the time taken to build relationships and engage them in a process of self‐assessment, planning, and decision making was constrained and rationed. The article concludes that to achieve a participatory children's space, an active and more engaged model of childhood needs to be facilitated by practitioners and parents outside the school‐dominated space found in this study.